Potential mechanism of traditional Chinese medicine intervention in gastric cancer: targeted regulation of autophagy - Sun, Siyuan; Yu, Wenqian; Zhang, Guangheng; Li, Xiangyu; Song, Linjing; Lv, Yehan; Chen, Yi (Frontiers in Pharmacology, 2025)
Gastric cancer (GC) is a prevalent malignant tumor that originates from the epithelial cells of the gastric mucosa, predominantly in the form of adenocarcinoma. Extensive research has confirmed the significant role of autophagy in the initiation, progression, and chemoresistance of GC. The potential of traditional Chinese medicine (TCM) to exert anti-tumor effects by modulating autophagy has been demonstrated, particularly in the context of GC prevention and treatment. Natural products (NPs) have great therapeutic potential in the prevention and treatment of GC by targeting autophagy-related genes and signaling pathways to intervene in the biological behaviors of gastric cancer cells such as proliferation, metastasis, invasion and death. This article describes the molecular mechanisms and key markers of tumor autophagy, the signaling pathways involved in GC-associated autophagy (PI3K/AKT/mTOR, AMPK, MAPK, p53), and summarizes the mechanism of autophagy and Helicobacter pylori infection in GC, how autophagy interacts with apoptotic and iron-death processes and the wide-ranging influences that these factors play in the process. Finally, this paper systematically summarizes the natural compounds of terpenoids, polyphenols, alkaloids, saponins, and polysaccharides that modulate autophagy-related signaling pathways and potential targets for the treatment of GC, and evaluates the toxic effects of NPs, providing a more compelling rationale and direction for GC therapy.